KAJIAN FAKTOR YANG DAPAT MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PROGRAM DESA MAJU INHIL JAYA (DMIJ) - Rezky Kinanda; Roberta Zulfhi Surya (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
The DMIJ program is a noble program from the Indragiri Hilir Regency Government to advance the villages in this district. The community is a welfare target as well as an element driving the success of the DMIJ program. This program is one of the government's flagship programs to advance villages in Inhil Regency. There are not many scientific studies have specifically addressed this program. There are actors who must work together in order to achieve the goal of this program. In addition, the factors that influence the success of this program must be maximized by these actors and implemented in a sustainable manner. This journal explained what matters should be the District Government in order to maximize the activities that will be carried out at the Integrated DMIJ Plus. This journal discussed how important the role of the community is in the DMIJ program and what factors can influence community participation. This journal is expected to become a consideration for the government to win the hearts of the people so that they are willing to work together to make the DMIJ program a success